Effect of Micro-sprinkler Irrigation on Growth, Yield and Water Use Efficiency of Different Agri-silvi-horti Systems - Kaushik, R.A.; Kaushik, N.; Kumar, Sushil (Indian Journal of Agroforestry, 2020)
The present studies were carried out at CCS Haryana Agricultural University, Regional Research Station, Bawal (Rewari), Haryana. Four tree species (Dalbergia sissoo, Emblica officinalis, Prosopis cineraria and Psidium guajava) were planted in September 2000 at a spacing of 6 x 6 m in 1:1 ratio. The inter space of the tree was cultivated with groundnut (Arachys hypogea), onion (Allium cepa), clusterbean (Cyamopsis tetragonaloba) fenugreek (Trigonella foenum graecum), ridgegourd (Luffa acutangula) tomato (Lycopersicon esculentum) rotation and irrigation at 100, 70 and 40% ETc (Evapotranspiration) was applied through micro-sprinkler. D. sissoo showed maximum plant height (456.7 cm) and diameter (9.7 cm) under 70% irrigation level. Minimum plant height (144 cm) and diameter (2.7 cm) was observed in P cineraria at 40% level of irrigation. The tree species showed significant differences for growth. Irrigation treatments were found significant only for diameter. The yields of intercrops were significantly affected by different irrigation levels and were highest at 100% irrigation level but it was not affected by differrnt tree species. The highest yield of 1010, 1360, 1730 kg/ha of groundnut, clusterbean and ridgegourd were recorded under D. sissoo + Psidium guajava, Prosopis cineraria + P guajava and P cineraria + E. officinalis respectively at 100% ETc irrigation level. During rabi season maximum yield offenugreek (2009 kg/ha) and tomato (40200 kg/ha) was observed under 100% ETc. The WUE increased as the level of irrigation decreased. This may be due to less water requirement under 70% and 40% irrigation levels and comparatively less reduction in yield under these levels of irrigation as compared to 100% irrigation level.